2005
DOI: 10.1111/j.1365-2621.2004.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Hot water and curing treatments reduce chilling injury and maintain post‐harvest quality of ‘Valencia’ oranges

Abstract: Valencia' oranges [Citrus sinensis (L.) Osbeck] were harvested at optimal maturity and either dipped in hot water at 53°C for 3 or 6 min or at 48°C for 12 min or cured at 53°C for 1 or 6 h or at 48°C for 12 h. The fruits were not degreened, waxed or treated with any post-harvest fungicides. All fruit samples were stored at 4°C for 6 months following the treatments. Both hot water dip and curing treatments reduced chilling injury and decay when compared with the untreated control. The most effective treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 20 publications
7
19
0
13
Order By: Relevance
“…These agree with the finding of a previous work that hot water and hot water incorporated with SA dip reduced the weight loss and the softening of rambutan fruit during storage (Supapvanich, 2015). Reducing weight loss and maintaining flesh firmness by heat treatment and exogenous SA application might due to maintaining and improving membrane function and reducing the activity of cell wall hydrolases (Erkan et al, 2005;Supapvanich and Promyou, 2013). Moreover, our previous works also found that hot water dip delayed the loss of firmness and weight loss of jujube fruit (Promyou et al, 2012) and 2.0 mM SA dip maintained membrane structure and retarded the softening of 'Kaek Dam' papaya fruit (Promyou and Supapvanich, 2016).…”
Section: Weight Loss Firmness and Tss Contentsupporting
confidence: 82%
“…These agree with the finding of a previous work that hot water and hot water incorporated with SA dip reduced the weight loss and the softening of rambutan fruit during storage (Supapvanich, 2015). Reducing weight loss and maintaining flesh firmness by heat treatment and exogenous SA application might due to maintaining and improving membrane function and reducing the activity of cell wall hydrolases (Erkan et al, 2005;Supapvanich and Promyou, 2013). Moreover, our previous works also found that hot water dip delayed the loss of firmness and weight loss of jujube fruit (Promyou et al, 2012) and 2.0 mM SA dip maintained membrane structure and retarded the softening of 'Kaek Dam' papaya fruit (Promyou and Supapvanich, 2016).…”
Section: Weight Loss Firmness and Tss Contentsupporting
confidence: 82%
“…Estos resultados concuerdan con un estudio realizado por Alférez et al (2005a), que puso de manifiesto que se producía una mayor pérdida de agua en frutos de naranjas del mutante 'Pinalate' con respecto a su parental 'Navelate' durante el almacenamiento en frío a pesar de que este mutante es menos susceptible a desarrollar 'daños de frío'. Además, concuerdan con resultados previos que mostraron que los tratamientos de calor aumentan la pérdida de agua y reducen la incidencia de 'daños de frío ' (McDonald et al, 1993a;Schirra et al, 2004;Erkan et al, 2005). Por tanto, la pérdida de agua no es un factor crítico en el desarrollo de síntomas de dicha alteración fisiológica como se había sugerido originalmente (Purvis, 1984;Cohen et al, 1994).…”
Section: Causas Y Morfologíaunclassified
“…Sin embargo, en nuestro caso este gen no parece tener un papel relevante en el efecto beneficioso del curado ni tampoco está asociado al daño. Aunque en otras variedades de frutos cítricos como pomelos se ha comprobado que la aplicación de ceras reduce la incidencia de 'daños de frío' (Wild, 1993;McDonald et al, 1993b;Dou, 2004;Bajwa y Anjum, 2007), los resultados obtenidos en este trabajo sugieren que los cambios en la expresión de genes implicados en la biosíntesis de ceras epicuticulares no están relacionados con el efecto beneficioso del curado y apoyan la idea de que el estrés hídrico no es un factor crítico en el desarrollo de 'daños de frío' en los frutos cítricos (McDonald et al, 1993b;Schirra et al, 2004;Erkan et al, 2005;Alférez et al, 2005a).…”
Section: Metabolismo De Lípidosunclassified
“…El acondicionamiento térmico es el tratamiento que ha demostrado ser más eficaz para incrementar la tolerancia al frío de los frutos cítricos, reduciendo además la incidencia de podredumbres durante el almacenamiento a bajas temperaturas y manteniendo su calidad (Lafuente et al, 1991;Lafuente et al, 1997;Porat et al, 2000;Plaza et al, 2003;Plaza et al, 2004;Erkan et al, 2005b).…”
Section: Efecto Del Acondicionamiento Térmico En La Carotenogénesisunclassified
“…El tratamiento térmico o acondicionamiento con aire caliente (entre 12 y 96 horas a temperaturas comprendidas entre 35 y 46 ºC) se desarrolló inicialmente para el control de hongos e insectos y para estudiar las respuestas de los productos a las altas temperaturas. Este tratamiento permite pasar los requisitos de cuarentena en frío (14 días a 1,5 ºC) a aquellas variedades sensibles a bajas temperaturas (Lurie, 1998;Schirra et al, 2004;Erkan et al, 2005b). Se ha demostrado que los tratamientos de curado son los más efectivos para un control no contaminante de la podredumbre postcosecha de los frutos cítricos (Plaza et al, 2004).…”
Section: Efecto Del Acondicionamiento Térmico En La Carotenogénesisunclassified